New Tubulin Inhibitors from Plants – A Critical Assessment - Jürg Gertsch; Sarah Meier; Natalie Tschopp; Karl-Heinz Altmann (CHIMIA, 2007)
The search for improved cytotoxic agents continues to be an important line of modern anticancer drug discovery and a promising mechanistic approach towards this goal is the functional inhibition of cellular microtubules. Tubulin inhibitors are compounds which either stabilize or destabilize microtubules in vitro, leading to G2/M cell cycle arrest and apoptosis in cancer cells. While destabilizing agents, such as vinca alkaloids inhibit the assembly of ??-tubulin heterodimers, stabilizing compounds like taxol induce the de novo formation of stable microtubules in vitro. In this study we have investigated a number of plant-derived compounds that have recently been reported to interact with the tubulin/microtubule system and to induce taxol-like effects. This includes the sesquiterpene lactones parthenolide and costunolide, the coumarin derivative ferulenol, and the jatrophane ester JTE1. In addition, we have screened a small natural product library (84 cytotoxic compounds) and 107 cytotoxic plant extracts in an assay sys- tem that allows the detection of both microtubule-stabilizing and -destabilizing agents in a 96-well setup within the same experimental format. None of the plant extracts inhibited or induced tubulin polymerization in vitro. From the compound library only the known plant-derived tubulin inhibitors vinblastine, colchicine, podophyllotoxin, chelidonine, rotenone, and taxol were identified as hits. Curcumin, which was recently reported to destabilize cellular microtubules, was inactive in our assay. Interestingly, rotenone, which is widely used as a mitochondrial respiration chain I inhibitor, potently inhibited microtubule assembly in vitro and showed higher affinity to ??-tubulin than vinblastine, although it was significantly less cytotoxic. None of the plant-derived natural products that were recently reported to be microtubule-stabilizing agents were found to be active in our assay system. In conclusion, plant-derived natural products clearly represent an interesting and productive source for microtubule-destabilizing agents. In contrast, apart from taxol and related structures, no plant-derived natural product with potent in vitro microtubule-stabilizing properties has yet been identified.